Linear and Star Poly(ionic liquid) Assemblies Surface Monolayers and Multilayers - Erwin, Andrew J (Langmuir : the ACS journal of surfaces and colloids, 2017)
The surface morphology and organization of poly(ionic liquid)s (PILs), poly[1-(4-vinylbenzyl)-3-butylimidazolium bis(trifluoromethylsulfonyl)imide] are explored in conjunction with their molecular architecture, adsorption conditions, and postassembly treatments. The formation of stable PIL Langmuir and Langmuir-Blodgett (LB) monolayers at the air-water and air-solid interfaces is demonstrated. The hydrophobic bis(trifluoromethylsulfonyl)imide (Tf2N-) is shown to be a critical agent governing the assembly morphology, as observed in the reversible condensation of LB monolayers into dense nanodroplets. The PIL is then incorporated as an unconventional polyelectrolyte component in the layer-by-layer (LbL) films of hydrophobic character. We demonstrate that the interplay of capillary forces, macromolecular mobility, and structural relaxation of the polymer chains influence the dewetting mechanisms in the PIL multilayers, thereby enabling access to a diverse set of highly textured, porous, and interconnected network morphologies for PIL LbL films that would otherwise be absent in conventional LbL films. Their compartmentalized internal structure is relevant to molecular separation membranes, ultrathin hydrophobic coatings, targeted cargo delivery, and highly conductive films